Shape and compliance of endothelial cells after shear stress in vitro or from different aortic regions: scanning ion conductance microscopy study. - Claire M F Potter; Sophie Schobesberger; Martina H Lundberg; Peter D Weinberg; Jane A Mitchell; Julia Gorelik (PLoS ONE)
Objective To measure the elongation and compliance of endothelial cells subjected to different patterns of shear stress in vitro, and to compare these parameters with the elongation and compliance of endothelial cells from different regions of the intact aorta. Materials and methods Porcine aortic endothelial cells were cultured for 6 days under static conditions or on an orbital shaker. The shaker generated a wave of medium, inducing pulsatile shear stress with a preferred orientation at the edge of the well or steadier shear stress with changing orientation at its centre. The topography and compliance of these cells and cells from the inner and outer curvature of ex vivo porcine aortic arches were measured by scanning ion conductance microscopy (SICM). Results Cells cultured under oriented shear stress were more elongated and less compliant than cells grown under static conditions or under shear stress with no preferred orientation. Cells from the outer curvature of the aorta were more elongated and less compliant than cells from the inner curvature. Conclusion The elongation and compliance of cultured endothelial cells vary according to the pattern of applied shear stress, and are inversely correlated. A similar inverse correlation occurs in the aortic arch, with variation between regions thought to experience different haemodynamic stresses.